2018
DOI: 10.1001/jamainternmed.2018.3675
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Safety of Discharging Select Patients Directly Home From the Intensive Care Unit

Abstract: IMPORTANCE The safety of discharging adult patients recovering from critical illness directly home from the intensive care unit (ICU) is unknown.OBJECTIVE To compare the health care utilization and clinical outcomes for ICU patients discharged directly home from the ICU with those of patients discharged home via the hospital ward. DESIGN, SETTING, AND PARTICIPANTSRetrospective population-based cohort study of adult patients admitted to the ICU of 9 medical-surgical hospitals from January 1, 2014, to January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(111 citation statements)
references
References 38 publications
4
104
1
Order By: Relevance
“…We realize that not all patients with SAH are eligible for the fast-track strategy; however, even using our conservative estimate of 18.0% of 30,000 SAH cases nationally, and applying similar ICU LOS cost savings ($3000/ d), 8 days saved would equate to a $158,400,000 cost savings for the SAH patients in the US health care system. Recently, Stelfox et al 18 reported similar ICU discharge to home safety and feasibility among a large cohort of 6732 ICU patients in a multicenter Canadian ICU system. They reported discharge from the ICU to home in 922 patients (13.7%) that was feasible and relatively safe for general medical conditions, with similar readmission rates.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We realize that not all patients with SAH are eligible for the fast-track strategy; however, even using our conservative estimate of 18.0% of 30,000 SAH cases nationally, and applying similar ICU LOS cost savings ($3000/ d), 8 days saved would equate to a $158,400,000 cost savings for the SAH patients in the US health care system. Recently, Stelfox et al 18 reported similar ICU discharge to home safety and feasibility among a large cohort of 6732 ICU patients in a multicenter Canadian ICU system. They reported discharge from the ICU to home in 922 patients (13.7%) that was feasible and relatively safe for general medical conditions, with similar readmission rates.…”
Section: Discussionmentioning
confidence: 91%
“…They reported discharge from the ICU to home in 922 patients (13.7%) that was feasible and relatively safe for general medical conditions, with similar readmission rates. 18 Our center is currently exploring a multicenter comparative effectiveness study to scale this model to other hospitals using similar inclusion and safety monitoring criteria to validate our preliminary data. In the future, we are also considering creation of an "UltraeFast-Track" SAH model with a potential discharge time of less than 7 days by using the same care process but focused on individualizing or using precision medicine for those patients with low mFS (1-2), who are at even lower risk for DCI and vasospasm and have no cerebrospinal fluid diversion requirements.…”
Section: Discussionmentioning
confidence: 99%
“…We used clinical and administrative databases from Alberta Health Services and Alberta Health (Discharge Abstracts Database [DAD], National Ambulatory Care Reporting System [NACRS], Physician Claims, Vital Statistics, and eCritical Tracer Database), previously successfully used in research studies [24,25]. eCritical Tracer is a bedside electronic medical record that prospectively captures demographic, clinical, and patient outcomes for all patients admitted to an Alberta ICU [26]…”
Section: Data Sourcesmentioning
confidence: 99%
“…16 For patients with multiple ICU admissions, only the rst admission was analyzed. The included ICUs were nine mixed medical/surgical units with a median [IQR] of 24 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] beds. Two units were classi ed as academic/quaternary, two were academic/tertiary units, and ve were community/metropolitan units ( Table 1).…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…The eCritical Alberta system provides high-quality data due to rigorous data quality assurance and auditing processes and has been used by our team previously in health services research. 4,[18][19][20][21] There were no missing data elements for our primary exposure and outcome (afterhours discharge and hospital mortality, respectively). Missing data for individual variables were <3% and were not replaced or imputed.…”
Section: Data Sourcesmentioning
confidence: 99%